Impact of the COVID-19 Pandemic on Ophthalmology Residency Training in Portugal - Silva, Nisa (2020)
Introduction: The purpose of this study was to provide objective and real-life data concerning the impact of the COVID-19 pandemicon ophthalmology residency training in Portugal.Material and Methods: Descriptive survey-based study applied to current Portuguese ophthalmology residents (n = 80 eligible).Results: Seventy-five residents participated (94% response rate). All except one (99%) admitted a change in their routine clinical practice during the pandemic, and most (89%) continued to be engaged in ophthalmology department duties. Twenty-five percent were deployed to COVID-19 units, which was combined with ophthalmological activities in about half of them (47%). A significant proportion of participants stated that they were enrolled in the following ophthalmological activities: emergency/inpatient care (87%), outpatient visits (73%; general 70% vs subspecialty 29%), and surgical procedures (64%). Twenty-five percent did not assist in any outpatient visits and 36% did not participate in any surgical procedures. On a scale from 1 (no impact) to 5 (maximum impact), most participants classified their perceived negative impact of the pandemic on the training program as 3 (24%), 4 (40%), or 5 (27%). Participants highly agreed with the extension of the residency program (80%) in order to to make up for training disruption.Discussion: Most trainees provided ophthalmological care during the pandemic. However, those clinical activities were essentially related to general and emergency care. Surgical experience was significantly curtailed. As such, strategies are needed to guarantee a high-quality learning process. Further studies are required to develop an international perspective on how ophthalmology training programs have been affected so that educational organizations can make recommendations regarding standardized adjustments to training programs.Conclusion: The COVID-19 pandemic has significantly impacted the training of ophthalmology residents nationwide.